The effect of recycled Polyethylene Terephthalate (PET) bottles waste as a fine aggregate replacement in concrete - Nadimalla, Altamashuddinkhan; Masjuki, Siti Aliyyah; Saad, Siti Asmahani; Othman, Nur Hawa; Amiruddin, Ahmad Kamil; Ali, Maisarah (2019)
This research aims to study the potential of PET bottles waste as a fine aggregate replacement in concrete. PET bottles waste was preferred because it is readily available, and it causes an environmental problem. The PET bottles waste was grinded into a fine particle which is similar to sand particle size. Then, it was partially replaced by sand with 0.5%, 1% and 1.5% in the concrete mix. This mix design is referred from the Department of Environment (DOE) method, and test specimen was cast for M30 grade concrete for 7-days,28-days, and 90-days. The performance of recycled PET bottles concrete were investigated based on several experimental methods such as slump test, compressive strength test and flexural strength test